The Virtual Reality of Our Healthcare System - Shaw, Aakash; Ren, Cathy (The Meducator, 2018)
Healthcare is an ever-advancing field that adapts new technologies and techniques to provide the most efficient and appropriate care for patients. Today, virtual reality (VR) may be the start of a paradigm shift for a multitude of healthcare services. VR is being studied as a safe and early intervention for rehabilitation and as a non-pharmacological analgesic option for patients recovering from accidents or motor neuron diseases. VR devices can prepare patients for physiotherapy or occupational therapy, which could significantly enhance therapeutic efficiency. As an analgesic, VR could prove to be an excellent alternative to overused medications. VR is also being employed for medical training to provide more immersive opportunities for students to practice their medical skills. This article examines how VR can contribute to these sectors of healthcare, highlights its impeding factors, and evaluates its potential.